2010
DOI: 10.1111/j.1463-1318.2009.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral rectopexy for external rectal prolapse improves constipation and avoids de novo constipation

Abstract: Ventral rectopexy has a recurrent prolapse rate of < 5%, similar to that of posterior rectopexy. Its correction of preoperative constipation and avoidance of de novo constipation appear superior to historical functional results of posterior rectopexy. A laparoscopic approach allows low morbidity and short hospital stay, even in those patients over 80 years of age in whom a perineal approach is usually preferred for safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
96
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 28 publications
(51 reference statements)
12
96
0
7
Order By: Relevance
“…Nevertheless, the post-operative mean hospital stay in our study was only 2 days, comparable with that reported by experienced centres [2,4,12].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Nevertheless, the post-operative mean hospital stay in our study was only 2 days, comparable with that reported by experienced centres [2,4,12].…”
Section: Discussionsupporting
confidence: 74%
“…Wijffels et al [3,12,[23][24][25][26] demonstrated the safety of this technique for the elderly compared with previously used more extensive procedures for rectal prolapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original articles by D'Hoore et al [6,7], the use of a polypropylene mesh is described, with distal fixation by nonresorbable sutures and proximal fixation by either nonresorbable sutures or an endofascia stapler. Since then, several articles [4,5,[8][9][10] have reported on the results of LVR for both internal and external rectal prolapse. A polypropylene mesh is used in all these studies, and the majority of the studies mention the use of tacks as the proximal mesh fixation technique of choice.…”
Section: Discussionmentioning
confidence: 98%
“…A few previous studies report that the laparoscopic procedure is effective and safe to perform on elderly debilitated patients [4,5], but often the study populations have mean ages close to 60-70 years [6][7][8], which in this setting may be considered young.…”
Section: Introductionmentioning
confidence: 96%